Mr. Mom in the News: The Relationship Between Stereotypes and Perceptions of Gendered News Stories. Issue 1 (2nd January 2017) - Hoewe, Jennifer; Appelman, Alyssa; Stevens, Elise
Abstract : This study examined the relationship between women's stereotypes and their perceptions of gendered news stories, specifically about stay-at-home parenthood. A between-subjects experiment with undergraduate women revealed that participants with stereotypes about women thought a news story about a stay-at-home mother was more typical than one about a stay-at-home father. Additionally, participants with stereotypes about women thought the news stories were low in realism, regardless of the story's gendered content. Notably, participants who read the news story about a stay-at-home father found it more enjoyable than the story about a stay-at-home mother, regardless of their stereotypes.